Musiques populaires et imaginaires latins en Extrême-Orient : Le Nakasi à Taïwan - Leonardo García (Centre de Recherches sur les Mondes Américains, 2014)
This paper analyses the diffusion of Latin imaginaries in Far-eastern Asia during the 20th Century through popular music and dance. An important part of these imaginaries are associated with the crossed cultural dynamics characterizing the development of Nakasi, an extremely popular music genre from Japan and Taïwan. We will approach here the different aspects of creation, circulation and consuming of a certain global Far-Eastern Latinity particularly in Taiwan, considering the references of a planetary record market as the evolution of local identities, national cultural models and social mobilities.